Pengajaran Dan Pembelajaran E-Learning Berbasis Schoology Selama Masa Pandemi Covid-19 - Zakaria, Yoyo (Institut Pendidikan Indonesia, 2022)
Abstract — This research is motivated by a view that the current competitive Vocational High School (SMK) educational institutions are in need of supplements for learning, especially understanding English subjects because the delivery of material is only in the form of text and the lack of use of internet-based learning media even though in schools already internet network available. This study aims to determine the feasibility of schoology-based e-learning as a product of teaching and learning and to determine differences in learning outcomes between students who use schoology-based e-learning and students who use text, this learning was carried out during the covid-19 pandemic. There is still a lack of understanding in English subjects because the delivery of material is only in the form of text and the lack of use of internet-based learning media. This research uses the research and development method or Research and Development (R&D) with reference to the research model from Borg & Gall which is simplified by the Puslitjaknov Team into 5 steps. The research process is: (1) Conducting product analysis to be developed, (2) Developing initial products, (3) Conducting small-scale field trials, (5) Large-scale field trials and making the final product. all test subjects are students of class X . This research took place at SMK Muhammadiyah 2 Kuningan in class X TKJ. the results of descriptive statistics from the two samples studied, namely the Pre Test and Post Test. For the pre-test value, the average test result or mean is 66.86. As for the Post Test value obtained an average value of 86.17. Because the average value of the Pre Test is 66.86 < Post Test 86.17, descriptively there is a difference in the average score of the English test between the Pre Test and Post Test.Keywords— learning media, e-learning, schoology, covid-19 pandemic Abstrak — Penelitian ini dilatarbelakangi oleh pandangan bahwa lembaga pendidikan Sekolah Menengah Kejuruan (SMK) yang kompetitif saat ini sangat membutuhkan suplemen untuk pembelajaran khususnya pemahaman mata pelajaran bahasa Inggris karena penyampaian materi hanya berupa teks dan kurangnya penggunaan. media pembelajaran berbasis internet padahal di sekolah sudah tersedia jaringan internet. Penelitian ini bertujuan untuk mengetahui kelayakan e-learning berbasis schoology sebagai produk belajar mengajar dan untuk mengetahui perbedaan hasil belajar antara siswa yang menggunakan e-learning berbasis schoology dan siswa yang menggunakan teks, pembelajaran ini dilaksanakan selama pandemi covid-19. Masih kurangnya pemahaman dalam mata pelajaran bahasa Inggris karena penyampaian materi hanya berupa teks dan kurangnya penggunaan media pembelajaran berbasis internet. Penelitian ini menggunakan metode penelitian dan pengembangan atau Research and Development (R&D) dengan mengacu pada model penelitian dari Borg & Gall yang disederhanakan oleh Tim Puslitjaknov menjadi 5 langkah. Proses penelitian adalah: (1) Melakukan analisis produk yang akan dikembangkan, (2) Mengembangkan produk awal, (3) Melakukan uji coba lapangan skala kecil, (5) Uji coba lapangan skala besar dan membuat produk akhir. semua subjek tes adalah siswa kelas X. Penelitian ini bertempat di SMK Muhammadiyah 2 Kuningan pada kelas X TKJ. hasil statistik deskriptif dari dua sampel yang diteliti yaitu Pre Test dan Post Test. Untuk nilai pre-test, rata-rata hasil tes atau mean adalah 66,86. Sedangkan untuk nilai Post Test diperoleh nilai rata-rata sebesar 86,17. Karena nilai rata-rata Pre Test adalah 66,86 < Post Test 86,17, maka secara deskriptif terdapat perbedaan nilai rata-rata tes bahasa Inggris antara Pre Test dan Post Test.Kata kunci— media pembelajaran, e-learning, schoology, pandemi covid-19